A Multisystemic Approach to the Prevention and Treatment of Child Abuse and Neglect - Swenson, Cynthia Cupit (Int J Child Maltreat, 2018)
Families experiencing physical abuse and/or neglect are at risk of continued difficulties that may involve long-term monitoring by Child Protective Services (CPS) and perhaps even removal of the child. Interventions needed to help the family remain intact safely and reduce both the clinical challenges they are experiencing and risk of further maltreatment will need to meet the multiple needs of all family members and involve a positive, collaborative working relationship with CPS. If services that are typically provided at outpatient clinics are used, the CPS case worker may be tasked with linking the family to many providers. When the family cannot make all the appointments, they are at further risk of removal of their child. In this article we present Multisystemic Therapy for Child Abuse and Neglect (MST-CAN), an ecologically based treatment for families experiencing physical abuse and/or neglect in which research-supported mental health services are delivered in the home by one clinical team to families who have serious clinical needs. To date, MST-CAN has been implemented with families experiencing the most serious levels of risk, but application is feasible for families with lower risk levels. Among high-risk families, MST-CAN has been shown effective for reducing out-of-home placement, abusive or neglectful parent behavior, and parent and child mental health difficulties and for increasing natural social supports. Two specialty population programs based on MST-CAN are also presented. These are MST – Building Stronger Families, a specialty program for parents who are experiencing abuse or neglect co-occurring with substance abuse, and MST for Intimate Partner Violence for families experiencing abuse or neglect and intimate partner violence. All models are based on the core Standard MST model. We trace the history of model development to dissemination.